Workshop Report: Governance of Emerging Nanotechnology Risks in the Semiconductor Industry - Watjanatepin, Ponnapat; Castagnola, Valentina; Cetin, Yüksel; Linkov, Igor; Skentelbery, Claire; Prodanov, Dimiter (Frontiers in Public Health, 2020)
Assessment of risk in the field of nanotechnology requires an integrated multidisciplinary approach due to the complex and cross-disciplinary framework for materials and activities at the nanoscale. The present paper summarizes the workshop “Governance of emerging nano-risk in the semiconductor industry” held on April 26, 2018 in Brussels, Belgium. The event targeted representatives of stakeholder communities involved in the risk assessment and governance of the engineered nanomaterials. Nanoelectronics was selected as an impactful use case for risk assessment approaches and comparison to bottom-up nanofabrication. The workshop outlined key data gaps impeding successful assessment of risks associated with nanoparticle use in the industry, using the semiconductor industry as an example. The workshop outlined mitigation strategies informing future regulatory decisions and identified some directions for future efforts.